Diplomasi Budaya dan Konservasi Laut di Coral Triangle Untuk Membangun Jembatan Kerjasama Regional - Zahra Dwi Wardhania; Agussalim Burhanuddin (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
The Coral Triangle, situated in the western Pacific Ocean, is famous for its exceptional natural wealth and abundant coral reefs, earning it the title of the "heart" of the world's coral reefs. This article emphasizes the significance of coral reef conservation within the Coral Triangle and explores the potential of cultural diplomacy in bolstering regional cooperation for conservation efforts. Through a literature review, the research aims to understand the role of cultural diplomacy in preserving coral reefs in this region, identifying gaps in knowledge for further investigation. Findings suggest that cultural diplomacy is pivotal in coral reef conservation by fostering international collaboration, raising awareness, and safeguarding traditional knowledge. Additionally, it aids in addressing ecological and economic challenges by promoting regional cooperation and sustainable tourism practices in the Coral Triangle. The research underscores the importance of cultural diplomacy and regional collaboration in preserving local heritage and ensuring environmental sustainability within the Coral Triangle, stressing the necessity of unified efforts to manage and protect coral reef ecosystems.